Aggression following benzodiazepine ingestion in a forensic psychiatric patient: a case report - Md Rosli, Ahmad Nabil Md Rosli; Singh, Suarn (ASEAN Federation of Psychiatry, 2015)
Objective: The incidence of benzodiazepine paradoxical reaction is uncommon. It may be implicated with crime as will be described in this case report. Method: We report a 37 year-old schizophrenia patient who was detained by the authority under Section 392/397 of Penal Code assaulting a lady using sharp weapon. He had history of illicit substance abuse and benzodiazepine dependence with significant history of aggression associated with benzodiazepine. Just prior to the incident, he took a significant amount of various types of benzodiazepine and suffered from amnesia of that event. During the time of the offense, he was in remission as far as schizophrenia is concerned. Result: He was under the forensic psychiatric care and observation at Hospital Bahagia Ulu Kinta (HBUK). He developed withdrawal symptoms of benzodiazepine in the ward. Conclusion: He was found by the expert team to be under the influence of benzodiazepine during the offence. The role of benzodiazepine and relevant factors leading to aggression will be discussed in this manuscript.